2022
DOI: 10.3390/ijerph19148673
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Personal Values and Intentions to Purchase Plant-Based Meat Alternatives: Application of the Dual Concern Theory

Abstract: This study examines consumers’ intentions to purchase plant-based meat alternatives (PBMA), which have been created to protect animal rights, the global environment, and consumers’ health. Data from 319 Korean consumers were analyzed to establish a causal relationship among personal values (egoistic, biospheric, and social-altruistic), the dual concern theory (anticipated positive effect and empathetic concern), and PBMA purchase intentions. Multigroup analysis was performed for all paths according to generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 61 publications
(153 reference statements)
0
1
0
Order By: Relevance
“…Personal values and attitudes have been recently identified by Bolwig et al (2021) among the main individual factors affecting food waste and sustainable food behaviors in general. Similarly, Jang and Cho (2022) showed how personal values positively affect consumers' intentions to purchase plant-based meat alternatives, while Gallagher et al (2022) revealed how individual attitude has a strong effect on intention to reduce food waste. Accordingly, the following hypotheses are proposed:…”
Section: 3mentioning
confidence: 99%
“…Personal values and attitudes have been recently identified by Bolwig et al (2021) among the main individual factors affecting food waste and sustainable food behaviors in general. Similarly, Jang and Cho (2022) showed how personal values positively affect consumers' intentions to purchase plant-based meat alternatives, while Gallagher et al (2022) revealed how individual attitude has a strong effect on intention to reduce food waste. Accordingly, the following hypotheses are proposed:…”
Section: 3mentioning
confidence: 99%